Human Resources Management in the Development of the Halal Industry: The Role of Entrepreneurship in Indonesia - Haqiqotus Sa’adah; Nur Asnawi (Budapest International Research and Critics University, 2022)
Indonesia has great potential as a center for the world's halal industry. The potential to get there already exists, ranging from halal certification, concern for Muslim-friendly products, services that make it easier for Muslims to practice their beliefs, and much more. The strategy to achieve Indonesia's vision as the world's leading halal economic center is by strengthening the value chain (halal value chain). In it, there are a number of industries that are the targets of Indonesia's halal economy master plan for 2019-2024 related to the needs of the world's Muslim community, one of which is the food and beverage industry, where Indonesia has abundant potential for the food and beverage industry. In this study using qualitative research methods with a normative juridical approach. While the data sources in this study were articles in journals related to the theme. The data collection technique was carried out by means of a literature review. The results in this study, namely, Rasulullah SAW, has made efforts to develop human resources. These efforts include: 1). Planning, 2). Withdrawal of human resources, 3). develop it so that it is of high quality, 4). Conduct performance appraisals, 5). Provide motivation and maintenance of human resources.